Systematic Literature Review Terhadap Evaluasi Perangkat Lunak Tentang Serious Game - Andhik Ampuh Yunanto; Siti Rochimah (LPPM Universitas Bina Sarana Informatika, 2017)
AbstrakSaat ini game merupakan perangkat lunak yang popular dikalangan anak-anak, remaja, dan dewasa. Selain itu, terdapat game yang memiliki tujuan tertentu selain sebagai media hiburan yang disebut dengan serious game. Banyaknya penelitian tentang serious game dapat membantu penelitian atau pengembang dalam melakukan manajemen atau pengembangan perangkat lunak game. Sehingga diperlukan adanya Review literatur tentang serious game agar informasi dapat terklasifikasi dan terkategori secara sistematis. Penelitian ini bertujuan untuk memberikan suatu informasi dengan melakukan Systematic Literature Review (SLR) terhadap penelitian-penelitian terkini tentang evaluasi serious game dari tahun 2015 sampai Oktober 2016. Metode SLR yang diusulkan memiliki tiga tahap Review yakni eksternal, internal, dan Sembilan quality assessment (QA). Hasil akhir yang diperoleh dalam penelitian ini menunjukkan terdapat 34 penelitian tentang serious game yang baik. Dari penelitian yang diReview juga menunjukkan bahwa penelitian tentang evaluasi serious game memiliki domain aplikasi edukasi, jenis game komputer, metode evaluasi kuesioner, evaluasi tentang kualitas hasil pembelajaran, prosedur evaluasi yang sederhana, dan jumlah populasi berkisar 1 orang sampai 50 orang. Hasil SLR yang telah didapatkan ini diharapkan dapat memberikan kontribusi dan informasi penting kepada peneliti atau pengembang yang tertarik di bidang serious game. Serta penelitian ini bermanfaat untuk meningkatkan kualitas serious game dalam memberikan pendidikan dan penyuluhan terhadap suatu komunitas di masyarakat. Kata kunci: Serious game, Evaluasi, Systematic Literature Review.AbstractGame is a software that is popular among children, adolescents, and adults. In addition, there are games that have a specific purpose other than as a medium of entertainment which called Serious Games. The amount of research on serious games can help developers in research, management, and software development in game. So it is necessary to Review the literature about the serious game so that information can be classified and categorized systematically. This study aims to provide an update by the Systematic Literature Review (SLR) to the recent studies on the evaluation of serious games from 2015 until October 2016. The proposed SLR method has three stages of Review that is external, internal, and nine quality assessment (QA). The final results obtained in this study indicate there are 34 research on serious games. From the studies that were Reviewed also show that research on the evaluation of serious games have educational applications domain, the type of computer games, methods of evaluation questionnaires, evaluation of the quality of learning outcomes, evaluation procedures are simple, and the number of populations ranging from 1 to 50 people. The results that have been obtained SLR is expected to contribute and important information to the researcher or developer interested in the field of serious games. This research can also improve the quality of the serious game for education and counseling in community. Keywords: Serious game, Evaluation, Systematic Literature Review AbstractGame is a software that is popular among children, adolescents, and adults. In addition, there are games that have a specific purpose other than as a medium of entertainment which called Serious Games. The amount of research on serious games can help developers in research, management, and software development in game. So it is necessary to Review the literature about the serious game so that information can be classified and categorized systematically. This study aims to provide an update by the Systematic Literature Review (SLR) to the recent studies on the evaluation of serious games from 2015 until October 2016. The proposed SLR method has three stages of Review that is external, internal, and nine quality assessment (QA). The final results obtained in this study indicate there are 34 research on serious games. From the studies that were Reviewed also show that research on the evaluation of serious games have educational applications domain, the type of computer games, methods of evaluation questionnaires, evaluation of the quality of learning outcomes, evaluation procedures are simple, and the number of populations ranging from 1 to 50 people. The results that have been obtained SLR is expected to contribute and important information to the researcher or developer interested in the field of serious games. This research can also improve the quality of the serious game for education and counseling in community. Keywords: Serious game, Evaluation, Systematic Literature Review